Cultural diversity, Intercultural Competence, Tolerance and the Economy: a Review - Alhendi, Osama (International Journal of Engineering and Management Sciences, 2021)
Cultural diversity is generally a controversial topic in the literature. Whereas some studies proved that it has economic benefits, others denied that. However, it is possible to avoid the costs related to that through enhancing each of intercultural competence, on the level of firms, and social tolerance, on the level of economies. To investigate that, the study used literature review analysis. Based on the literature, cultural diversity plays important role in enhancing innovation and entrepreneurship which are necessary for economic development. However, it may result in different challenges such as a lack of trust and conflict. Therefore, it could be feasible to manage and benefit from cultural diversity in the companies through cross-cultural training as well as cultural diversity management. On the other hand, economies can avoid cultural diversity's costs by adopting the policies and institutions which are necessary for enhancing the level of social tolerance among people.